The Molecular Epidemiology and Antimicrobial Resistance of Neisseria gonorrhoeae in Australia: A Nationwide Cross-Sectional Study, 2012. (28th September 2016) - Trembizki, Ella; Wand, Handan; Donovan, Basil; Chen, Marcus; Fairley, Christopher K.; Freeman, Kevin; Guy, Rebecca; Kaldor, John M.; Lahra, Monica M.; Lawrence, Andrew; Lau, Colleen; Pearson, Julie; et al.
Abstract : In this nationwide study of Neisseria gonorrhoeae and associated antimicrobial resistance, Australia 2012, we showed that infections are dominated by relatively few strain types and that particular strain types were concentrated among females. Abstract : Background. Antimicrobial resistance (AMR) by Neisseria gonorrhoeae is considered a serious global threat. Methods. In this nationwide study, we used MassARRAY iPLEX genotyping technology to examine the epidemiology of N. gonorrhoeae and associated AMR in the Australian population. All available N. gonorrhoeae isolates (n = 2452) received from Australian reference laboratories from January to June 2012 were included in the study. Genotypic data were combined with phenotypic AMR information to define strain types. Results. A total of 270 distinct strain types were observed. The 40 most common strain types accounted for over 80% of isolates, and the 10 most common strain types accounted for almost half of all isolates. The high male to female ratios (>94% male) suggested that at least 22 of the top 40 strain types were primarily circulating within networks of men who have sex with men (MSM). Particular strain types were also concentrated among females: two strain types accounted for 37.5% of all isolates from females. Isolates harbouring the mosaic penicillin binding protein 2 (PBP2)—considered a key mechanism for cephalosporin resistance—comprised 8.9% of all N. gonorrhoeae isolates and were primarily observed in males (95%). Conclusions. This large scale epidemiological investigation demonstrated that N. gonorrhoeae infections are dominated by relatively few strain types. The commonest strain types were concentrated in MSM in urban areas and Indigenous heterosexuals in remote areas, and we were able to confirm a resurgent epidemic in heterosexual networks in urban areas. The prevalence of mosaic PBP2 harboring N. gonorrhoeae strains highlight the ability for new N. gonorrhoeae strains to spread and become established across populations.